KESESUAIAN LOKASI TPA BOJONGLARANG DAN ALTERNATIF PEMBANGUNAN TPA BARU DI KABUPATEN PEKALONGAN - Nikmanti, Ikmah Artin; Pigawati, Bitta (Program Studi Perencanaan Wilayah dan Kota, Fakultas Teknik, Universitas Semarang, 2024)
Waste is the one of serious problems faced by every city because the quantity continues increase along with population growth. Pekalongan is one of city that still has problem related to waste management. The only landfill in Pekalongan, (Bojonglarang landfil)l is already overload. This causes the need for expansion or build the new landfill in Pekalongan. The research aims to analyze the suitability of the Bojonglarang landfill location and analyze other alternative locations suitable for new landfills in Pekalongan. Use a quantitative descriptive method with a spatial approach with GIS. The results show that the location of the Bojonglarang Landfill is less suitable based on location and carrying capacity. The research show that there are 5 locations that most suitable for the new landfill in Pekalongan. These locations include Sawangan Village, Bligorejo Village, Gejlig Village, Kesesi and Ujung Negoro Villages, and Pedawang and Legokkalong Villages. It is expected to be input for Pekalongan Government regarding policies related to landfills problem in Pekalongan.